Effectiveness of Application of Techniques In Teaching Sociology: Enhancing Understanding of Society through Modern Teaching Techniques (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Society-based  research  subjects  are the  study  of  sociology which  is an  importantbranch of science in the field of social science. It is a branch of studying society, social values, social groups, social classes and economical, political, social, religious, lawfulinstitutions, population, usage, custom, value, norm, beliefs and relations and changesbetween  them. In this context, sociology gains sociological thinking skill with its own peculiar methodology, and therefore it helps complex social events to be understoodbetter. Giving the faculty of looking at sociological events with the eye of sociology and sociological thinking to individuals in educational process in early ages will enable thefaculty of  „understanding‟  of  society  and social  events to  be more established  andsystematic. It is an urgent need of using teaching methods and techniques leading to critical sight which is the basement of sociology, instead of passive student                             profileresulting  from                use     of     traditional        teaching   methods  and   techniques  in                teachingsociology. It is known well that as a need of modern education understanding, thisrequirement exists physically in teaching programs but educators are in difficulty of application  of new  techniques.  The main goal  of this study  is to  emphasize the application of modern teaching techniques in teaching sociology actively. For this reason, application of producing ideatechniqueisgoing to be realized in teaching of sociology. Key words: Teaching of sociology, modern teaching techniques, producing idea.